An Outbreak of Synthetic Cannabinoid-Adulterated Tianeptine Products in New Jersey – Case Series - Christopher J. Counts; Anthony V. Spadaro; Trevor A. Cerbini; Alex J. Krotulski; Sara E. Walton; Howard A. Greller; Lewis S. Nelson; Bruce E. Ruck; Oliver Hung; Barry Logan; Diane P. Calello (Journal of Medical Toxicology, 2025)
Background Tianeptine, an atypical antidepressant not approved in the United States, is readily purchased from unregulated markets such as the internet and gas stations. We became aware of a cluster of 34 patients in New Jersey who became ill following ingestion of the tianeptine containing-product Neptune’s Fix, the rate of which (4.6 cases per month) far exceeded the background rate for this substance of 0.5 cases per year. Methods We retrospectively identified tianeptine exposures reported to the New Jersey Poison Information and Education System (NJPIES) prior to June 2023 to determine the background rate of tianeptine exposure. From June 2023– February 2024 we prospectively surveilled tianeptine exposures reported to NJPIES, recorded demographic and clinical information, and recruited samples for testing. Six samples of the ingested products were obtained and analyzed using gas chromatography mass spectrometry (GC-MS) and liquid chromatography quadrupole time-of-flight mass spectrometry (LC-QTOF-MS). Whole blood samples from two patients were tested for tianeptine and synthetic cannabinoids. Results During the period of interest, NJPIES received 41 exposure calls, with 37 reporting acute toxicity in 34 unique patients, two reporting chronic tianeptine use, and two reporting withdrawal. Among the 37 exposures resulting in acute toxicity, commonly reported effects included altered mental status, tachycardia, hypotension, and seizures. 43% ( n = 16) were intubated, and 65% ( n = 24) were admitted to the ICU. Analytical testing of six samples identified variable product composition, containing various xenobiotics including tianeptine, kava alkaloids, natural cannabinoids, and the synthetic cannabinoids MDMB-4en-PINACA and ADB-4en-PINACA. MDMB-4en-PINACA was detected in one of the two patient blood specimens. Conclusions These cases represent a marked increase in tianeptine exposures compared with the poison center’s historical average. Analytical testing revealed variable product composition, including the presence of synthetic cannabinoids. Clinicians should be aware that tianeptine containing products are widely available, unregulated, and can be adulterated.